SISTEM INFORMASI BERBASIS PEMROGRAMAN BERORIENTASI OBYEK UNTUK PENGADAAN BAHAN BAKU PADA CV. AINTZANE MANDIRI - Indra Ava Dianta; Nuris Dwi Setiawan; Tofani Wulandari (STEKOM PRESS, 2020)
CV Aintzane Mandiri is a company engaged in the field furniture. The Raw Material Manager at CV Aintzane is not yet optimal. Purchase Raw materials need to be considered because they will affect the maturity raw material needs and affect the production process. The information system for the supply of raw materials is needed by the company determination of expenditure, input of raw materials, and can minimize supply of raw materials for optimal use throughout the process production. Designing and building a procurement information system using raw materials Material Requirement Planning (MRP) method with programming language Microsoft Visual Basic 6.0, WAMP as server and MySQL as database. The results obtained from this information system can be obtained planning raw material requirements and production optimally and accordingly with company expectations. Keywords : Materials Requirement Planning, Computerized Accounting, Wamp, MySql